Further Evidence on the Role of Thyroid Autoimmunity in Women with Recurrent Miscarriage - Natalia Lazzarin; Costanzo Moretti; Giovanna De Felice; Elena Vaquero; Dario Manfellotto (International Journal of Endocrinology)
It has been twenty years since the first paper reporting the association between thyroid antibodies (TAIs) and spontaneous miscarriage was published. Following this observation, several studies have clearly demonstrated an increased prevalence of TAI in patients with recurrent miscarriage (RM). However, the exact mechanism underlying this association remains a matter of debate. The aim of the present study was to evaluate the thyroid function, throughout a specific test, in patient with RM and TAI focusing on the hypothesis that TAI should be an indirect sign of a mild thyroid dysfunction. 46 patients with RM and TAI were included in the study. All patients underwent short TRH stimulation test showing an abnormal response in the vast majority of cases (65%). Normal FT4 and FT3 mean values were found whereas TSH values were in the upper normal range (2.64±1.3 mUI/L). Our data support the hypothesis that in patients with RM the presence of TAI is an indirect sign of a subtle thyroid dysfunction detectable by a specific test. This test give the possibility to identify women with RM in which specific therapeutic approaches could effectively improve the possibility for a successful pregnancy.